Basic math help
Hugh Senior
h at FlexibleLearning.com
Sun Feb 21 03:47:19 EST 2010
Thank you, Peter...
My school days are long gone too. However, I came up with this:
GW = (n * MW) + [(n - 1) * 25]
GW = (n * MW) + (n * 25) - 25
GW + 25 = (n * MW) + (n * 25)
GW + 25 = n * (MW + 25)
n = (GW + 25) / (MW + 25)
Now back on track!
/H
>Can anyone help me out, perhaps off list, with re-jigging this equation in
terms of n?
>
>GW = (n * mW) + [(n-1) * 25]
>
>I've tried but my school days are too long ago!
>
>/H
More information about the use-livecode
mailing list